Fréquence des rétractations d’articles scientifiques : ce que les études nous apprennent en éducation, sciences humaines et sciences sociales - Roy-Vallières, Maude (Canadian Journal of Education/Revue canadienne de l'éducation, 2021)
Article retractions are science’s last resort to ensure its own credibility. This study aims at identifying reasons that lead scholars to investigate retractions in their own scientific domain. To that end, a literature review, as well as a qualitative analysis thereof, were carried out. Results show that 70 % of retraction studies were conducted in the natural and medical sciences domain. Eight reasons for retraction interest were found, the most frequent being negative impact on research and practice, highly publicized fraud cases and high annual number of publications. Results help justify retractions studies’ prevalence in the natural and medical sciences domain but raise the need for further retraction studies and for establishing comprehensive databases in other research fields to ensure high quality scientific research.